In Vitro Anti-cholinesterase and Cognitive Enhancing Properties of Essential Oils from Piper nigrum L. and Monodora myristica (Gaertn) Dunal - I J, Olawuni; S A, Ndoni; E E, Esada; F S, Bamidele; E M, Obuotor (International Journal of Pharmacology and Toxicology, 2018)
Aging in humans generally is associated with deterioration of cognitive abilities, particularly of learning and memory leading to dementia, including Alzheimer’s disease. A number of herbal medicines are reported to improve brain function and intelligence. In the present study, the ameliorating effects of essential oil extracted from Piper nigrum and Monodora myristica on learning and memory in Scopolamine induced amnesic mice were determined using two cognitive behavioural paradigms: the Step-Through Passive Avoidance and Morris-Water Maze test. Essential oils were obtained by hydro-distillation using a Clavenger-type apparatus and their profiles analyzed by GC-MS. Inhibitory effects on AChE and BuChE were investigated by Ellman’s method. The animals were assessed for performance by measuring the Step-Through Latency Time (SLT) and Escape Latency Time (ELT). Brain cholinesterase activities were assayed in brain tissues from the mice. The results showed that M. myristica and P. nigrum oils were characterized by 51 (94.76%) and 61 (90.65%) components, respectively. M. myristica is dominated by α-phellandrene (18.13%), while P. nigrum is dominated by β-pinene (5.92%) and caryophyllene (4.55%). Both oils at 416 µg/ml elicited significant inhibitory (p>0.05) activity with M. myristica exhibiting a stronger inhibition against AChE and BuChE than P. nigrum. This trend was also exhibited significantly (p>0.05) in both ELT and the SLT when compared to scopolamine-treated group. In conclusion, the seeds of M. myristica and P. nigrum are potential sources of active metabolites with anti-cholinesterase and cognition enhancing properties, but M. myristica exhibited a higher activity.